Base pairing involving artificial bases in vitro and in vivo. Issue 2 (10th November 2015) - Bande, Omprakash; Braddick, Darren; Agnello, Stefano; Jang, Miyeon; Pezo, Valérie; Schepers, Guy; Rozenski, Jef; Lescrinier, Eveline; Marlière, Philippe; Herdewijn, Piet
Abstract : Herein we report the synthesis, base pairing properties and in vivo transliteration of N 8 -glycosylated 8-aza-deoxyguanosine and 8-aza-9-deaza-deoxyguanosine nucleotides with 8-amino-deoxyinosine, 1- N -methyl-8-amino-deoxyinosine and 7, 8-dihydro-8-oxo-deoxy-inosine/adenosine/guanosine as pairing partners. Abstract : Herein we report the synthesis of N 8 -glycosylated 8-aza-deoxyguanosine ( N 8 -8-aza-dG) and 8-aza-9-deaza-deoxyguanosine ( N 8 -8-aza-9-deaza-dG) nucleotides and their base pairing properties with 5-methyl-isocytosine (d-isoC Me ), 8-amino-deoxyinosine (8-NH2 -dI), 1- N -methyl-8-amino-deoxyinosine (1-Me-8-NH2 -dI), 7, 8-dihydro-8-oxo-deoxyinosine (8-Oxo-dI), 7, 8-dihydro-8-oxo-deoxyadenosine (8-Oxo-dA), and 7, 8-dihydro-8-oxo-deoxyguanosine (8-Oxo-dG), in comparison with the d-isoC Me :d-isoG artificial genetic system. As demonstrated by T m measurements, the N 8 -8-aza-dG:d-isoC Me base pair formed less stable duplexes as the C:G and d-isoC Me :d-isoG pairs. Incorporation of 8-NH2 -dI versus the N 8 -8-aza-dG nucleoside resulted in a greater reduction in T m stability, compared to d-isoC Me :d-isoG. Insertion of the methyl group at the N 1 position of 8-NH2 -dI did not affect duplex stability with N 8 -8-aza-dG, thus suggesting that the base paring takes place through Hoogsteen base pairing. The cellular interpretation of the nucleosides was studied, whereby a lack of recognition or mispairing of the incorporated nucleotides with the canonical DNA bases indicated the extent of orthogonality in vivo . The most biologically orthogonal nucleosides identified included the 8-amino-deoxyinosines (1-Me-8-NH2 -dI and 8-NH2 -dI) and N 8 -8-aza-9-deaza-dG. The 8-oxo modifications mimic oxidative damage ahead of cancer development, and the impact of the MutM mediated recognition of these 8-oxo-deoxynucleosides was studied, finding no significant impact in their in vivo assay.